The Gothic and the Everyday Living Gothic - Piatti-Farnell, L.; Beville, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The Gothic and the Everyday aims to regenerate interest in the Gothic within the experiential contexts of history, folklore, and tradition. By using the term 'living', this book recalls a collection of experiences that constructs the everyday in its social, cultural, and imaginary incarnations.
Keywords: Communication; Literature, Modern—18th century; Civilization—History.; Literature—Philosophy.; Culture—Study and teaching; Social sciences; Media Studies; Eighteenth-Century Literature; Cultural History; Literary Theory; Cultural Theory; Social Sciences, general